Climatic Controls on C4 Grassland Distributions During the Neogene: A Model-Data Comparison - Fox, David L.; Pau, Stephanie; Taylor, Lyla; Strömberg, Caroline A. E.; Osborne, Colin P.; Bradshaw, Catherine; Conn, Stephen; Beerling, David J.; Still, Christopher J. (Frontiers in Ecology and Evolution, 2018)
Grasslands dominated by taxa using the C4 photosynthetic pathway evolved on several continents during the Neogene and Quaternary, long after C4 photosynthesis first evolved among grasses. The histories of these ecosystems are relatively well documented in the geological record from stable carbon isotopes (fossil vertebrate herbivores, paleosols) and the plant microfossil record (pollen, phytoliths). The distinct biogeography and ecophysiology of modern C3 and C4 grasses have led to hypotheses explaining the origins of C4 grasslands in terms of long term changes in the Earth system, such as increased aridity and decreasing atmospheric pCO2. However, proxies for key parameters of these hypotheses (e.g., temperature, precipitation, pCO2) are still in development, not yet widely applied, and/or remain contentious, so testing the hypotheses globally remains difficult. To understand better possible links between changes in the Earth system and the origin of C4 grasslands, we undertook a global scale comparison between observational records of C4 grass abundances in Miocene and Pliocene localities compiled from the literature and three increasingly complex models of C4 dominance and abundance. The literature compilation comprises >2,600 δ13C values of both fossil vertebrates and of paleosol carbonates. We forced the vegetation models with simulated monthly climates from the HadCM3 family of coupled ocean-atmosphere GCMs over a range of pCO2 values for each epoch to model C4 dominance or abundance in grid cells as months per year exceeding the temperature at which net carbon assimilation is greater for C4 than C3 photosynthesis (crossover temperature model); the number of months per year exceeding the crossover temperature and having sufficient precipitation for growth (≥25 cm/yr; Collatz model); and the Sheffield Dynamic Global Vegetation Model (SDGVM), which models multiple plant functional types (C3 and C4 grasses, evergreen and deciduous trees). Model-data agreement is generally statistically weak, suggesting that regional to local ecological interactions, continent specific plant evolutionary histories, and/or regional to local climatic conditions not represented in global scale GCMs may have been equally as strong or stronger in driving the evolution of C4 grasslands as global changes in the Earth system.